UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA POKOK BAHASAN TEOREMA PYTHAGORAS MELALUI PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Hidayati, Nisa Nurul (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2022)
The purpose of this study was to improve learning outcomes of mathematics subjects on the subject of the Pythagorean Theorem in class VIII-5 SMPN 12 Tarakan by using the jigsaw method. Based on the observations, it was found some of the students' weaknesses in learning mathematics. These weaknesses were the lack of interest and motivation of students when participating in the learning process in class, mathematics subject teachers did not fully implement innovative learning, low student learning outcomes in class on the subject of the Pythagorean Theorem, and lack of student activity in participating in learning activities in the classroom. This research was a classroom action research. The success rate of students was more than 80% of students in the class reach a score of 70. The stages of the research include the planning, action implementation, and reflection stages for each cycle. This research stopped in the third cycle because in the third cycle it had reached the success criteria. Based on the results of the study, it was found that there was an increase in learning outcomes which after the action in the third cycle was obtained the results of 87.5% of students in the class got a score of 70. Thus it can be concluded that jigsaw learning can improve student learning outcomes.